Relationship between parenting rearing behavior and mobile phone dependence among college students： the mediating role of emotional intelligence - Zhang Jianhua; Zhao Yifan; Dong Jinjin; Yang Shichang (Sichuan jingshen weisheng, 2021)
ObjectiveTo investigate the prevalence rate of mobile phone dependence， and to analyze the mediating role of emotional intelligence between parenting rearing behavior and mobile phone dependence among college students， so as to provide references for relieving the mobile phone dependence among college students.MethodsStratified cluster sampling method was applied to enroll 1 200 students from three colleges in He'nan province， and the selected individuals were assessed using Parental Bonding Instrument （PBI）， Mobile Phone Addiction Index （MPAI） and Emotional Intelligence Scale （EIS）. Then the relationship between parenting rearing behavior and mobile phone dependence was discussed， and the mediating effect of emotional intelligence was explored using AMOS path analysis.ResultsOf the students who completed the survey， 597 out of 1 090 （54.77%） suffered from mobile phone dependence. The scores of care and encouragement of behavioral freedom in PBI were negatively correlated with the total score and each dimension score of MPAI （r=-0.316~-0.197， P<0.01）， the denial of psychological autonomy score in PBI was positively correlated with the total score and each dimension score of MPAI （r=0.206~0.258， P<0.05 or 0.01）. EIS score was negatively correlated with total score and each dimension score of MPAI （r=-0.317~-0.219， P<0.01）. The indirect effect sizes of maternal care， encouragement of behavioral freedom and denial of psychological autonomy on mobile phone dependence through emotional intelligence were 47.98%， 47.00% and 42.93%， respectively. The indirect effect sizes of paternal care， encouragement of behavioral freedom and denial of psychological autonomy on mobile phone dependence through emotional intelligence were 47.99%， 48.71% and 44.70%， respectively.ConclusionEmotional intelligence partially mediates the relationship between parental rearing behavior and mobile phone dependence.